Effect of the Problem-Solving Approach on Academic Achievement of Students in Mathematics - Khadka, Madan Singh; Thagunna, Puskar Singh (Far Western Review, 2025)
The primary focus of this quantitative experimental study was to explore the effect of the problem-solving approach on the academic achievement of students in mathematics at grade IX and to compare the achievement of boys and girls of grade IX taught using this method at Latinath Secondary School Naugad 03, Darchula. This study was based on experimental research method under the quantitative research design. A sample of 60 students was chosen using purposive stratified random sampling, forming equivalent experimental and control groups of 30 students each. Data were collected using two achievement tests (pre-test and post-test) and structured interview tools. Statistical calculations included mean, standard deviation, two-tailed t-test, and coefficient of variation (CV). The post-test results indicated a significant difference in mean achievement between the groups (mean difference of 4.44), significant at the 0.05level. The coefficient of variation of the achievement of students in the control group (18.14%) was higher than that of the experimental group (12.20%). It was concluded that the experimental group, taught with the problem-solving approach, had better achievement than the control group, which was taught using the traditional approach. Furthermore, while the mean achievement score of boys (30.08) was slightly greater than that of girls (29.68) in the post-test, the difference was not statistically significant at the0.05 level. Thus, the study concluded that the problem-solving approach minimizes the gender difference in learning mathematics.